“We LOVE the way you think” winner: The Apple and the Mannequin (International Journal of First Aid Education)
Summarizes the International First Aid Education Conference's "We LOVE the way you think" competition and the winning pitch, by Emily Stang, to use produce and mannequins in hands-on class participation so as to foster discussion and engagement amongst students while learning about wound care.